Sustainable wine – for whom? Consumer preferences for different environmental labels - Tommaso Fantechi; Caterina Contini; Nicola Marinelli; Marco Moriondo; Sergi Costafreda-Aumedes (Wine Economics and Policy)
As sustainability concerns increasingly influence agri-food systems, environmental labels have become an important tool for signalling producers’ ecological responsibility to consumers. However, the effectiveness of such labels depends on how they are perceived and valued in specific product contexts. This study investigates consumer preferences for four environmental labels in the wine sector: organic certification, carbon neutral, reduced water footprint, and reduced pesticide use. A discrete choice experiment conducted with 300 Italian wine consumers, combined with latent class analysis, revealed four distinct segments with heterogeneous responses to environmental labels. While one group rejected environmental labels altogether, others displayed selective interest based on the perceived relevance of the label to specific concerns such as health or resource conservation. These findings highlight the need for tailored communication strategies that take into account both consumers’ cultural associations with wine – such as tradition, authenticity, and artisanal value – and their individual priorities, including differing levels of engagement with various aspects of environmental sustainability. In a category as culturally embedded as wine, where tradition, identity, and quality perceptions play a central role, tailored messaging becomes especially crucial to ensure that environmental-labels are understood, trusted, and valued.